2018
DOI: 10.21037/jtd.2018.02.82
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of predictive factors regarding prognoses and invasion of thymic neuroendocrine tumors preoperatively and postoperatively

Abstract: Background: Thymic neuroendocrine tumors (TNT), in the anterior mediastinum, are extremely rare diseases which have significantly poor prognoses. Studies have rarely provided conclusive evidence of the prognostic factors of TNT. Standard therapies have been controversial. Methods: TNT patients (n=173) were enrolled from Surveillance, Epidemiology and End Results database (SEER). Univariate and multivariate analyses were utilized to evaluate predictive factors of prognoses.Logistic regression analysis was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A definite conclusion could not be made whether radiotherapy and chemotherapy helped improve survival [21,[26][27][28][29], although it is generally accepted that TNET are more aggressive than thymomas, and adjuvant radiotherapy is now mostly recommended for aggressive thymomas. Corsini et al found that neither radiation nor chemotherapy impacted OS (p = 0.594, p = 0.234) [16].…”
Section: Discussionmentioning
confidence: 99%
“…A definite conclusion could not be made whether radiotherapy and chemotherapy helped improve survival [21,[26][27][28][29], although it is generally accepted that TNET are more aggressive than thymomas, and adjuvant radiotherapy is now mostly recommended for aggressive thymomas. Corsini et al found that neither radiation nor chemotherapy impacted OS (p = 0.594, p = 0.234) [16].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic factors of surgical treated thymomas are (17,18). It is worth noting that thoracic surgeons ignore the LND before, which influences the accuracy of TNM staging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated independent predictive factors of thymoma including age, Masaoka stage, WHO pathologic grade, resected marginal status, and adjuvant therapies ( 2 , 4 , 13 - 16 ). Besides, patients with myasthenia gravis could influence survival ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a large population retrospective database, SEER has its limitations inevitably. It does not include the details of recurrence ( 16 ). Fortunately, as an indolent tumor, the distant recurrence rate of thymoma is extremely low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation